New York Transplant Teams Versus COVID-19. (September 2020) - Blackstock, Daryle; Butler, Laura; Delair, Samantha; Dokus, Katherine; Eileen, Farrington; Carolyn, Forman; Helen, Irving; Carrie, Lindower; Tania, Lyons; Nancy, Metzler; Janine, Morris; Brigitte, Sullivan; et al.
New York State, and especially New York City, were hit hard by the coronavirus disease 2019 (COVID-19) virus. While we followed its course in other parts of the world, and began preparations, there was no way we could have been prepared for the volume and severity of illness that began to overflow in our emergency departments and hospital units. We expanded intensive care units into our medical surgical units while turning conference rooms into medical surgical patient care areas. Clinicians at the bedside described war-like situations with numerous patients arresting and requiring ventilator support. Our New York consortia and organ procurement organizations met online 3 times a week and shared creative strategies to address clinical care and work processes. We would like to share strategies from what we hope was a once in a lifetime experience.